The Roles of Islamic Content Quality and Physical Attractiveness of Muslim Influencer on Social Media Consumption: Likeability as Mediator - Robiansyah Robiansyah; Khusnul Khotimah; Aisyah Trees Sandy; Saida Zainurossalamia (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
This study examines the role of Muslim influencers in presenting high-quality Islamic content and influencer physical attractiveness on social media consumption, with a focus on the mediating effect of influencer likeability. Drawing on Uses and Gratifications Theory (UGT), the research contributes to theory development by exploring how Muslim influencers fulfill the social and religious needs of their audience through engaging content and physical attractiveness. The study targets 396 public university students who actively engage with influencer content on social media. Structural Equation Modeling (SEM-PLS) confirms that influencer likeability significantly mediates the relationship between Islamic content quality, physical attractiveness, and social media consumption. The findings show that both Islamic content quality and physical attractiveness positively influence likeability, which in turn enhances social media consumption. From a theoretical perspective, this research advances UGT by highlighting how religious and cultural factors shape media consumption in the digital age. Managerially, it provides marketers and content creators with insights on balancing content quality and influencer physical attractiveness to boost engagement and consumption, particularly in culturally and religiously sensitive markets.